The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1183/23120541.00298-2022
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of comorbidities on initial combination therapy in pulmonary arterial hypertension

Abstract: RationaleDemographic characteristics of pulmonary arterial hypertension (PAH) patients have changed over time, but the effects of cardiovascular risk factors on risk status and pulmonary vascular resistance (PVR) reduction with initial oral combination therapy are not known. Therefore, we tested the relevance of cardiovascular comorbidities in this setting.MethodsThe study enrolled 181 treatment-naive PAH patients with a 6-months (IQR 144–363 days) right heart catheterization and risk assessment after initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
1
3
0
2
Order By: Relevance
“…It suggested that initial combination therapy with ERA + PDE5i is able to improve WHO functional class (WHO-FC), exercise capacity, and N-Terminal pro-B-type Natriuretic Peptide (NT-proBNP) at 6 months (weaker response in patients with cardiovascular risk factors). These data were consistent with those of the above mentioned AUMC analysis and those of the AMBITION study [36].…”
Section: Targeted Pah Therapy For Ipah Patients With Significant Como...supporting
confidence: 92%
See 1 more Smart Citation
“…It suggested that initial combination therapy with ERA + PDE5i is able to improve WHO functional class (WHO-FC), exercise capacity, and N-Terminal pro-B-type Natriuretic Peptide (NT-proBNP) at 6 months (weaker response in patients with cardiovascular risk factors). These data were consistent with those of the above mentioned AUMC analysis and those of the AMBITION study [36].…”
Section: Targeted Pah Therapy For Ipah Patients With Significant Como...supporting
confidence: 92%
“…The authors concluded that there are no compelling reasons to withhold targeted PAH treatment from patients with pre-capillary PH diagnosed as IPAH and significant comorbidities or additional risk factors for LVDD. Another retrospective analysis [36] in 181 patients with IPAH, CTD-PAH and CHD-PAH from the Italian Pulmonary Hypertension Network (iPHNET) database assessed the impact of comorbidities on hemodynamic and clinical response to initial oral combination therapy. It suggested that initial combination therapy with ERA + PDE5i is able to improve WHO functional class (WHO-FC), exercise capacity, and N-Terminal pro-B-type Natriuretic Peptide (NT-proBNP) at 6 months (weaker response in patients with cardiovascular risk factors).…”
Section: Targeted Pah Therapy For Ipah Patients With Significant Como...mentioning
confidence: 99%
“…Despite the fact that some experts might call this case PH secondary to group 2 or group 3 disease, whereas others might classify this case as IPAH with cardiopulmonary comorbidities, the outcome is poor, irrespective of the name of the disease. This group of P(A)H patients experienced less effective responses from mono or combination therapies compared to “classic” PAH patients without (cardiopulmonary) comorbidities [ 113 , 114 ]. In addition, the first group of patients may experience higher rates of clinical failure [ 114 ].…”
Section: Casementioning
confidence: 99%
“…Die Analyse des COMPERA-Registers zeigte ein Therapieansprechen mit Verbesserung des Risikoprofils bei 34 % der Patient*innen mit 3-4 Komorbiditäten, 33 % bei 1-2 Komorbiditäten im Vergleich zu 52 % bei PAH-Patient*innen ohne kardiale Komorbiditäten [14]. Bei Einsatz einer initialen Kom- binationstherapie von ERA und PDE5-I scheinen PAH-Patient*innen mit kardialen Komorbiditäten gemäß Daten des italienischen Patient*innenregisters etwas geringer auf die Therapie anzusprechen als Patient*innen ohne kardiovaskuläre Risikofaktoren [15].…”
Section: Kombinationstherapien Bei Pah Und Komorbiditätenunclassified
“…Daten zur Wirksamkeit spezifischer PAH-Medikamente bei Patient*innen mit Komorbiditäten stammen insbesondere aus Patient*innenregistern und Post-hoc-Analysen großer Therapiestudien. Aktuelle Analysen von Registerdaten deuten auf eine Wirksamkeit PAH-spezifischer Medikamente bei PAH-Patient*innen mit kardialen Komorbiditäten hin 14 15 16 . Die Analyse des COMPERA-Registers zeigte ein Therapieansprechen mit Verbesserung des Risikoprofils bei 34 % der Patient*innen mit 3–4 Komorbiditäten, 33 % bei 1–2 Komorbiditäten im Vergleich zu 52 % bei PAH-Patient*innen ohne kardiale Komorbiditäten 14 .…”
Section: Kommentar Zu Den Leitlinienunclassified